E-migrant women entrepreneurs: mobile money apps, transnational communication and the maintenance of social practices - Aderibigbe,Ireoluwa Deborah (Centre for Film and Media Studies, 2023)
This study set out to investigate how mobile money apps facilitate the maintenance of interpersonal relationships and transnational communication practices among migrant women entrepreneurs. Mobile money apps such as MamaMoney, MoneyTrans and Mukuru are a form of communication that are relevant and beneficial to the unbanked migrant women entrepreneurs in South Africa. The main research question was: how do mobile money apps facilitate the maintenance of interpersonal relationships and transnational communication practices among migrant women entrepreneurs? The methodology was informed by a feminist qualitative approach to three focus group discussions with fifteen participants from Nigeria, Zimbabwe and the Democratic Republic of Congo. A thematic analysis of transcriptions of focus group discussions was conducted and two broad themes were identified. The first broad theme explores the communicative dimensions of money transfer through mobile money apps by migrant women entrepreneurs, particularly in relation to their roles as mothers, daughters, sisters and friends in the diaspora. The second broad theme is the use of mobile money apps to solicit emergency funds and financial support during the COVID-19 pandemic. Findings indicate that mobile money apps have reshaped communication practices of migrant women entrepreneurs by enhancing interpersonal communication and facilitating social practices. Furthermore, the COVID-19 pandemic emphasized the two-way nature of bonds of mutual support amongst migrants. This study also draws on the idea of remittance scripts (Carling, 2014). Remittance scripts are a helpful way to conceptualise remittances as social transactions that take several different forms. The theoretical frameworks used in this dissertation are reverse remittances (Mazzucato, 2011), networked individualism (Raine and Wellman, 2012) and polymedia (Madianou and Miller, 2013). The importance of reverse remittances during the COVID-19 period highlights reciprocal bonds of social saving when eMWEs used mobile money apps to solicit financial help and emergency relief when they were unable to work due to the COVID-19 outbreak in South Africa. Reverse remittances also highlight the shift in power relations and the need for communication between eMWEs' and their families and friends at home. As suggested by Kusimba et al., (2015) the application of networked individualism in modern African societies is used in this study to understand how mobile money apps have afforded eMWEs with personal communication channels in addition to household-centred communication around money. Polymedia is used in this study to understand how eMWEs use mobile money apps in conjunction with the complementary affordances of other platforms such as WhatsApp, Instagram and Facebook, which compensate for limitations of mobile money apps.